Efeitos de um programa de atividade física em grupo em idosos com comprometimento cognitivo leve da estratégia saúde da família de Porto Alegre - Langoni, Chandra Da Silveira (2018)
LANGONI, Chandra da Silveira. Effects of a group physical activity program in older adults with mild cognitive impairment in the Family Health Strategy of Porto Alegre. 2018. 158f. Thesis (PhD in Biomedical Gerontology) – School of Medicine, Pontifical Catholic University of Rio Grande do Sul, Porto Alegre, Brazil, 2018. Mild cognitive impairment (MCI) presents high conversion rates to dementia, a disease of high prevalence in the elderly. The search for measures that prevent or delay this progression is necessary, such as physical exercise. However, randomized and controlled studies that determine the effects of physical exercises are still scarce. Therefore, in the present thesis, two original articles are presented, which describe the findings from a single blind, randomized and matched-pair controlled trial (sex, age, body mass index and Addenbrooke Cognitive Examination score). The sample consisted of 52 sedentary older adults with MCI, Family Health Strategy / Primary Health Care users from Porto Alegre/RS (Brazil), who were randomized into intervention group (IG) and control group (CG). For 24 weeks, the IG participated in two weekly meetings (60 minutes each) of aerobic and muscular strength exercises in group, while the CG maintained its usual routine. The instruments applied before and after the intervention were: Mini Mental State Examination (MMSE); 2-minute stationary walk test (SW); 30-second sit/stand test; functional reach test (FRT); Berg Balance Scale (BBS); Time Up and Go Test (TUG); Geriatric Depression Scale-15 (GDS-15). Prior to the intervention, the IG and CG did not differ statistically in any of the analyzed variables. In the first article, the effects of the exercise program on the cognitive function, conditioning, strength and balance of the participants were determined. In the intra-group analysis, the IG showed a significant increase in the mean MMSE scores (21.9±4.8x25.0±4.7), sit/stand repetitions (9.3±2.0x11.6±2.0), FRT distance (28.1±7.8x30.7±7.1) and the median number of SW steps [97.5(60.0-124.0)x131.5(105.0-153.8)], while the CG showed a significant reduction in the mean MMSE scores (23.7±3.7x20.4±4.1) and the FRT (30.6±8.2x27.1±6.9), after the intervention. The IG gains presented medium to large effect sizes, while in the CG the reductions in the MMSE and FR had large and medium effect size, respectively. In the between-group analysis, the IG presented mean scores of MMSE, SW and sit/stand significantly higher. In the second article, the effects of the exercise program on the balance, mobility and depressive symptoms (DS) of the older adults were determined. In the intra-group analysis, the IG presented significant reductions in the mean TUG time (10.7±2.9x8.3±2), median GDS-15 scores [4(1.8-6)x2.5(1-4)] and the frequency of DS [11(42.3%)x5(19.2%)]. in addition to a significant increase in the mean BBS scores (53±3x55.1±1.1), after the intervention. In the CG, a significant increase in the median GDS-15 scores [3.5(2-7.3)x4(2-5.3)] was observed. The IG presented gains in BBS and TUG, as well as a reduction in the frequency of DS with large effect sizes, while in the CG effect sizes between small and medium were detected for these variables. In the intra-group analysis, the IG showed significantly higher mean BBS scores and significantly lower TUG execution times than the CG. It is concluded that the exercise program improved cognitive function, aerobic conditioning, muscle endurance, balance, mobility and DS in older adults with MCI.